Exploring the roles of extensive reading on Malaysian tertiary ESL students motivation to read in English - Ker-Hsin, Wan; Razali, Abu Bakar (Human Resource Management Academic Research Society, 2022)
English language reading skills and reading motivation are important in tertiary education. In the case of Malaysian tertiary education, most courses are conducted in English language and most references are in English. However, Malaysian tertiary students’ reading proficiency in English has often been labelled as below par, which is attributed to poor reading skills and habits, as well as a lack of motivation to read. One of the ways that can increase their reading habits and motivation is extensive reading. This qualitative study explores Malaysian tertiary ESL students’ perceptions of extensive reading, the roles that extensive reading play in developing (or hindering) their reading motivation, as well as the factors that contribute to (or hinder) their motivation for reading. Employing a case study approach, three tertiary ESL students from three private institutes of higher learning in Klang Valley were selected via purposive sampling. Semi-structured individual interviews were conducted, and the participants’ reading journal entries were collected, and analysed using thematic analysis. The findings indicated that extensive reading was perceived to have great value, and it played important roles that developed participants’ motivation to read. However, sociocultural factors contribute to increasing or decreasing students’ motivation to read. It was found that students’ motivation to read can be developed and sustained when they believe in the value of extensive reading, have high expectancy for success at reading, and enjoy reading for its own sake as evidenced by their reports of experiencing flow while reading. The study also provide a better understanding of what drives students to read or hinders them from reading, which could allow valuable insight into motivating alliterates to read.